The Effect of Production and Sales Costs on Net Profit (Study of Pharmaceutical Companies Listed on the Indonesia Stock Exchange for the Period 2013-2021) - Rarassatika Ainunnisa; Julfan Herliansyah Noor; Farid Arifin (Lembaga Penelitian dan Pendidikan (LPP) Mandala, 2025)
This research aims to determine the effect of production and sales costs on net profit. The object of this study is the annual financial statements of pharmaceutical sub-sector manufacturing companies listed on the Indonesia Stock Exchange (IDX) for the 2013-2021 period which were recorded by 10 companies, but only 9 companies (81 financial statements) were used as samples based on criteria that had been planned and made by researchers. The research method used in this study is a descriptive and verifiable method with quantitative approach. The analytical tools used are multiple linear regression and coefficient of determination, to test a hypothesis, namely by using the T test and the F test. Then, the data processing process of this study used the IBM SPSS Statistic 16 Program. The results of the study showed in the T test that there is a partial influence between production costs on net profit and there is an influence between sales and net profit. Based on the results of the F test simultaneously variableproduction and sales costs affect net profit.